2019
DOI: 10.3164/jcbn.19-22
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gut microbiota in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL)

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a major hereditary small vessel disease caused by mutations in NOTCH3. The variations in progression and severity among patients suggest that the CADASIL phenotype is modified by some genetic and environmental factors. Recent studies have shown the potential roles of gut microbiota in human diseases. We hypothesized that gut microbiota modifies the disease phenotype. We performed gut microbial meta 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…On the contrary, the association between stroke and body mass index, raised cholesterol, or elevated serum homocysteine was not demonstrated in CADASIL (Adib-Samii et al, 2010). Interestingly, a recent study found significant taxonomic differences in gut microbiota between CADASIL patients and controls, suggesting a possible role of gut microbiota in influencing disease onset and progression, but more research is needed to confirm this hypothesis (Matsuura et al, 2019). The role of cardiovascular risk factors could be particularly important in EGFR 7-34 mutated individuals, who needs additional risk factors for the classical CADASIL phenotype to develop, while mutations in EGFR 1-6 may have a strong enough effect to cause the disease.…”
Section: Molecular Findingsmentioning
confidence: 93%
“…On the contrary, the association between stroke and body mass index, raised cholesterol, or elevated serum homocysteine was not demonstrated in CADASIL (Adib-Samii et al, 2010). Interestingly, a recent study found significant taxonomic differences in gut microbiota between CADASIL patients and controls, suggesting a possible role of gut microbiota in influencing disease onset and progression, but more research is needed to confirm this hypothesis (Matsuura et al, 2019). The role of cardiovascular risk factors could be particularly important in EGFR 7-34 mutated individuals, who needs additional risk factors for the classical CADASIL phenotype to develop, while mutations in EGFR 1-6 may have a strong enough effect to cause the disease.…”
Section: Molecular Findingsmentioning
confidence: 93%
“…There is a single study that focuses on the analysis of the microbiome in CADASIL patients, where the gut microbiome of 15 Japanese CADASIL patients and 16 controls was evaluated [ 52 ]. CADASIL patients were divided according to whether they had suffered a symptomatic ischemic stroke ( n = 7) or not ( n = 8).…”
Section: Omic Studies and Progress In The Etiopathogenesis Of Cadasilmentioning
confidence: 99%
“…There was no significant difference in vascular risk factors or nutritional items between CADASIL patients and the controls. The only significant difference was the daily intake of arachidonic acid between CADASIL subgroups, as patients with stroke had a lower intake ( p = 0.03) [ 52 ].…”
Section: Omic Studies and Progress In The Etiopathogenesis Of Cadasilmentioning
confidence: 99%
See 2 more Smart Citations